Application of the SAP2000 computer programme in the modelling of an underground quarry of dimension stone (Rudarsko-geološko-naftni zbornik, 2023)
A numerical analysis of part of the underground quarry of dimension stone with designed maximum dimensions of the rooms was carried out with the SAP2000 software based on the finite element method. The main objective of the analysis was to examine the preliminary stability and the influence of excavation on the redistribution of stresses in the surrounding rock masses, thus confirming the applicability of the tributary area method. The analytical solution with the tributary area method showed satisfactory agreement with the numerical calculations, and the results of the analytical calculations were on the safe side. The obtained results confirmed the predicted behaviour of the rock mass, which confirms the use of SAP2000 as a general-purpose software for civil engineering in the field of mining. The highest concentrations of stresses and strains are found in the edge areas of the pillars, so their correct design is crucial. The safety factor of the point with the highest stresses was determined and a value of 2.21 was obtained, thus fulfilling the stability condition. As for the influence on the surrounding area, stress changes of less than 10% were determined based on the solutions for the vertical stresses at a distance of 20 m from the underground excavation.